S81 Does adherence to inhaled therapy change following initiation of mepolizumab in the treatment of severe asthma?. (December 2018) - d'Ancona, G; Liu, B; Wei, L; Green, L; Fernandes, M; Roxas, C; Osman, L; Kavanagh, J; Jackson, DJ; Kent, BD
Abstract : Introduction and objectives: Anti IL-5 agents are used in addition to routine therapies: inhaled corticosteroids (ICS), long acting beta2 -agonists (LABA), long acting muscarinic antagonists (LAMA), Leukotriene Receptor Antagonists (LRTA), and short acting beta2 -agonists (SABA), in patients with severe eosinophilic asthma. They aim to improve disease control and reduce exacerbation frequency, where a good response is as defined as a 50% reduction in oral corticosteroid (OCS) use. The effect of stepping down or withdrawing routine medicines is unknown, and consequently, patients are advised to continue them. Clinical improvement may however lead some patients to modify treatments themselves. We assessed if adherence changed between the 12 months before and after initiation of mepolizumab. Methods: Patients with severe eosinophilic asthma requiring either maintenance OCS or recurrent short courses of OCS were commenced on mepolizumab 100 mg 4-weekly. The treating physician adjusted the patient's OCS dose according to response; however, other medicines were left unchanged. We used primary care prescription records in the 12 months preceding and succeeding the initiation of mepolizumab to calculate adherence (number of doses issued on prescription/expected number of doses to be used). OCS use was determined from patient reported usage and nurse recorded doses. Results: We reviewed the prescription records of 104 patients (age 52.7 (range: 21–80 years); 56.7% female), of whom 77 (74.0%) were receiving maintenance glucocorticoid therapy. Mepolizumab treatment led to a significant reduction in the number of OCS courses from 3/year to 0.5/year (p<0.0001) and SABA inhaler use showed a statistically significantly reduction of 1.1 actuations per day (p=0.032). There was no statistically significant change in adherence to therapy in the year before and after initiation for ICS/LABA (Δ4.2%; p=0.950), LAMA (Δ10.1%; p=0.865), or SABA nebules (Δ0%; p=0.968). See table 1. Conclusion: As the treating physician only adjusted the patient's OCS dose (where appropriate), other alterations were patient-led. One year of mepolizumab treatment did not appear to significantly affect how patients used their maintenance ICS/LABA or LAMA inhalers; however, SABA inhaler use declined significantly, a very re-assuring finding given the significant reduction in OCS use.